Ecoinfluencers' engagement with social media for a greener world / Bhavna Wal - Wal, Bhavna (Faculty of Information Management, 2023)
A fairly young phenomenon, social media's popularity with evergrowing acceptance has already hit the roof in the third decade of the present century in India. Emphasizing its role in people's lives as means of instant communication, exchanging thoughts and concepts finds space in public domain. As it is Gen Z are environmentally conscious, Indian ecoinfluencers use their ecoliteracy to spread the word. As content creators, leading by example, they acquire and upgrade knowledge, associate with eco-friendly brands for suitable content, using their social media influence to work for environmental concerns. Their content has impacted people to adopt green practices in their daily lives. Statement of the problem is how ecoinfluencers lead society to a greener living. The two objectives of the studyare to assess how ecoinfluencers create and use content impacting people for eco conservation and to investigate the reach of their influence across communities. The research paradigm for the study is analyzing through content analysis how communities can be impacted by ecoinfluencers for a sustainable living. Secondary data have been used for the study. One finding shows that ecoinfluencers, born story tellers, lead by self-emulation and second finding reveals that these influencers have been successful in inspiring people and achieving 'greener community' by displaying their unique and original content. In general conclusion it can be said that ecoinfluencers play a positive role for achieving a greener environment. This study is of paramount significance as it illuminates the transformative influence of ecoinfluencers in fostering a collective commitment to eco-conservation and sustainable living, thereby shaping a greener future.